ANALISIS KINERJA ORGANISASI PADA KANTOR KECAMATAN PALUPUH - Rahmad Rahmad; Nova Yarsina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: In the era of decentralization and regional autonomy, the performance of public organizations has an important role in providing public services to the community. Palupuh District is a public organization located in Agam Regency, West Sumatra Province. Palupuh District has the task of implementing the wheels of government and public services at the sub-district level. In achieving these goals, it is certainly influenced by the performance of the organization as a whole. This study aims to analyze how the Palupuh District organization performs in achieving its goals according to its vision and mission. To see the performance of Palupuh District, researchers look at various aspects, namely, productivity, responsiveness, service quality, cooperation, use of resources and punctuality. The second objective is to describe the inhibiting factors of Palupuh District organizational performance. This study is a qualitative descriptive study referring to the concept of performance indicators plus the conditions that exist at the research locus. Based on the results of the study, it can be explained that the performance of the organization has been running well, such as in the indicators of responsiveness, service quality, cooperation and punctuality. The indicators that still have obstacles are human resources and infrastructure. Therefore, researchers provide suggestions to improve human resource competency, optimize existing facilities and infrastructure to support activities and increase budget allocation and adjust according to budget targets.Keywords: Organizational Performance, Productivity, Use of Resources and Infrastructure.